SPECIFIC ASPECTS OF AVIBACTERIUM PARAGALLINARUM INACTIVATION WITH FORMALDEHYDE AND THIOMERSAL - M. S. Firsova; V. A. Yevgrafova; A. V. Potekhin (Ветеринария сегодня)
The paper demonstrates results of testing different modes of Avibacterium paragallinarum inactivation with formaldehyde and thiomersal. The bacterium destruction by 0.20% and 0.10% formaldehyde proceeds at the constant rate thus indicating exponential dependence of the microorganism inactivation processes. This fact allows for calculation of the inactivation rate constant that amounts to 2.94 ± 0.37 h-1 for 0.10% formaldehyde and 5.86 ± 0.72 h-1 for 0.20% formaldehyde. Inactivation using formaldehyde at final concentration of 0.10% at 37 °С and continuous stirring (60 rpm) produces 7.0 dm3 of bacterin at concentration of 9.5 ± 0.2 lg microbial cells (mc)/cm3 in 4.3 ± 0.1 h. Thiomersal demonstrated bactericidal action against Avibacterium paragallinarum at concentration of 0.04% (1:2500) or higher. Herewith, inactivation process is specified by linearity and the inactivation rate constant amounts to 7.92±1.12 h-1. Under thiomersal sublethal concentration of 0.2% (1:5000) the survival curve is of irregular shape. However, the process of the microorganism death is not exponential, and under continuous decrease, the inactivation rate is going to zero thus making impossible the calculation of the inactivation rate constant. Inactivation mode involving use of 0.04% thiomersal at 37 °С allows production of 7.0 dm3 of bacterin at 9.5 ± 0.2 lg mc/cm3 concentration in 5.8 ± 0.1 h. Right after production, the hemagglutination activity of the thiomersal inactivated antigen was higher as compared to formaldehyde inactivated antigen (Р  0.05). The antigen produced using formaldehyde maintains high hemagglutination activity during storage that is critical for high quality vaccine production.